2013
DOI: 10.2147/ccid.s41537
|View full text |Cite
|
Sign up to set email alerts
|

Onset and duration of effect of incobotulinumtoxinA, onabotulinumtoxinA, and abobotulinumtoxinA in the treatment of glabellar frown lines: a randomized, double-blind study

Abstract: BackgroundThree botulinum neurotoxin type A preparations (incobotulinumtoxinA, onabotulinumtoxinA, and abobotulinumtoxinA) are widely approved in Europe and in the US for the treatment of glabellar frown lines. The purpose of this study was to determine and compare the time to onset and duration of treatment effect of incobotulinumtoxinA, onabotulinumtoxinA, and abobotulinumtoxinA for the treatment of glabellar frown lines.Subjects and methodsSubjects aged 20–60 years with moderate to severe glabellar frown li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
(41 reference statements)
3
47
0
Order By: Relevance
“…10 In addition, a recent analysis suggested that incobotulinumtoxinA may have a more rapid onset and longer duration of action compared with onabotulinumtoxinA. 11 The goal of the present case report was to provide initial data regarding an alternative botulinum agent in the treatment of chronic migraine.…”
Section: Introductionmentioning
confidence: 92%
“…10 In addition, a recent analysis suggested that incobotulinumtoxinA may have a more rapid onset and longer duration of action compared with onabotulinumtoxinA. 11 The goal of the present case report was to provide initial data regarding an alternative botulinum agent in the treatment of chronic migraine.…”
Section: Introductionmentioning
confidence: 92%
“…Despite these distinctions and anecdotal observations that these products are not interchangeable, clinical studies remain inadequate and have failed to demonstrate consistent substantive differences between neurotoxins. 622 Limited data suggest that incobotulinumtoxinA has a more rapid onset and longer duration, 10 whereas abobotulinumtoxinA has greater spread, 11 and onabotulinumtoxinA has greater strain reduction. 12 Importantly, all neurotoxins elicit similar positive effects on patients’ self-perception of appearance.…”
Section: Neuromodulatorsmentioning
confidence: 99%
“…(1) IncobotulinumtoxinA (marketed under the trademark Xeomin®) has been shown to be effective for the treatment of glabellar frown lines (GFLs). (3)(4)(5)(6) It contains only the active neurotoxin and none of the complexing proteins commonly found in other BoNT/A products. As these complexing proteins are not required for the neurotoxin activity, incobotulinumtoxinA has a higher specific biologic activity in each dose.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Thus, the onset of treatment effect is more rapid for incobotulinumtoxinA as compared to other variants of BoNT/A. (6) A multicentre European study found that overall treatment satisfaction in using incobotulinumtoxinA specifically for GFLs was high among physicians and patients. (3) The drug was also well tolerated and had a longer duration of effect, permitting a gap of five months or more between injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation